A Real World Analysis of Safety and Efficacy of Nilotinib when Used as First Line and Beyond: Retrospective Single Centre Study Representing Largest Cohort of Indian Patients Treated with Nilotinib - Kumar, Sujeet; Singh, Anil; Singh, Neha; Faizi, Akbar Inam; Mishra, Bal Krishna; Gupta, Avinash; Yadav, Anil Kumar (Asian Pacific Journal of Cancer Biology, 2024)
Background: Efficacy and toxicity of TKIs may vary depending on the ethnic background or genetic factors; hence it is important to gather data from individual populations pertaining to each drug. The pivotal registration trial had not enrolled any patient from India and there are very limited published studies on its efficacy as well as safety from Indian patients with CML. Methods: Hospital Electronic Medical Record was screened for adult (age > 18 years) CML patients registered (n = 1290) at our hospital from 1st May 2018 to 31st December 2022. CML-CP or CML-AP patients, those who have received Nilotinib as 1st line (n = 40) or 2nd line (n = 66) or 3rd line TKI (n = 20) for at least 90 days (3 months) and have at least one RQ PCR BCR: ABL value post Nilotinib initiation, were enrolled in this study (n = 126). Results: Eighty (74.1%) patients achieved BCR/ABL of ≤ 1% at 12 months. MMR and MR4 at 12 months was seen in 44 (40.7%) and 19 (17.6%) patients respectively. The most common haematological toxicity was thrombocytopenia of any grade seen in 54 (42.8%) patients. Conclusion: Our study demonstrates that treatment with Nilotinib was well-tolerated in Indian patients and was effective in achieving molecular remission rates in 1st, 2nd or 3rd line therapy in the real-world setting. Safety and efficacy were in line with published western or Asian studies.